Automatic Refilling Machine - Mohammad Al-Amin, Salleh (UTeM, 2009)
Automatic refilling machine (ARM) wills a new innovation manufacturing industry especially sector filling. Automatic refilling machine is commercial refilling system that involves Programmable Logic Controller (PLC) and microcontroller. The system operates automatically in three stations, which are refilling, checking, and feedback. Filling system operated by automatic follow bottle height respectively. While system detector operated to detect deep table of contents stated bottle. In case happened error to table of contents stated bottle, bottle would be sent to system replenishment through the system feedback. For bottle also experience as many times surveillance process to three will be removed to place isolation. PLC operates to control DC motor as conveyer and pneumatic valve through signal forwarded by IR sensor. Microcontroller will obtain signal from IR sensor and data will be displayed on Liquid Crystal Display (LCD) .The LCD and Light Emitting Diode (LED) will be used to display amount of product produce, throw and system security.